До питання збереження та відновлення культурного ландшафту навколо дерев’яної церкви Святого Духа у селі Потеличі - Козак, Г.; Козак, І.; Стемпень, А.; Kozak, H.; Kozak, I.; Stempien, A. (Волинський національний університет імені Лесі Українки, 2012)
Показано краєзнавчу цінність села Потелича Жовківського району Львівської області з дерев’яною церквою Святого Духа. Запропоновано сучасні способи відновлення (зокрема нові технології тривимірної візуалізації) та збереження ландшафту навколо сакральної дерев’яної пам’ятки.In the work there was shown local history value of Potelycz village of Zhovkva region, Lviv district taking into account wooden church of Holy Spirit. Contemporary techniques of restoration (including innovative 3D visualization technologies) and maintenance of landscape around sacral wooden monument were presented as well.
Сoncerning the Question of Maintenance and Renewal of Cultural Landscape Around Wooden Church of Holy Spirit in Potelycz Village
Keywords: культурна спадщина; культурний ландшафт; тривимірна візуалізація; cultural heritage; cultural landscape; 3D visualization